Implementasi Pasal 7 Ayat (1) dan (3) UU No. 14 Tahun 2008 tentang Keterbukaan Informasi Publik dalam Pelayanan Pemerintah - Zahara, Juwita; Yolanda, Astri Ruli; Maharani, Ledina; Nemas, Inge; Jainah, Zainab Ompu (FOCUS, 2024)
This research examines the regulations surrounding Public Information Disclosure, which mandates that public institutions in Indonesia furnish and manage public information as part of their governmental duties. The purpose of this study is to analyze the normative aspects and practices of implementing public body obligations that are the object of Article 7 Paragraphs (1) and (3) in providing and managing public information. The research method used is normative juridical. From the results of the study, it can be concluded that Article 7 paragraphs 1 and 3 of the KIP Law have normative aspects and implementation of public body obligations. The results of the study indicate a gap between the legal norms regulated in the KIP Law and their implementation in the field. The juridical analysis identified several inhibiting factors, including diverse legal interpretations, limited supporting legal infrastructure, and lack of harmonization between the KIP Law and other sectoral regulations. The conclusion of the study is that effective implementation of Article 7 of the KIP Law requires a comprehensive approach involving legal reform, institutional strengthening, and increasing legal awareness of government officials and the public towards more transparent and accountable governance.